Industrial training report: JomRun Sdn. Bhd - Ahmad Zamzur, Nurul Amirah (Faculty of Business and Management, 2023)
During my 6-month industrial training as a Marketing Intern at JomRun Sdn. Bhd., I had the opportunity to gain hands-on experience in various marketing activities. Under the guidance of Puan Norazamimah, my lecturer at UiTM Bandaraya Melaka, and Ms. Jasmine Tan Qian Hui, my supervisor at JomRun, I received invaluable support and mentorship. JomRun Sdn. Bhd., a prominent company in the Malaysian Running Apps industry, provided me with an immersive learning experience. As a marketing Intern, I actively participated in market research, con ten t creation, ticketing services, and digital advertising. These activities not only deepened my understanding of marketing strategies but also honed my communication, team work, and problem-solving skills. Throughout the training, I conducted a SWOT analysis for JomRun Sdn. Bhd., identifying its strengths, weaknesses, opportunities, and threats. While the company's reputation as a leading running organizer was a notable strength, there were areas for improvement, such as addressing past event cancellations. Additionally, potential opportunities, such as securing trusted sponsorships, were identified, alongside threats from competing organizations. Based on the analysis, we engaged in comprehensive discussions to explore strategies for leveraging strengths, addressing weaknesses, capitalizing on opportunities, and mitigating threats. These discussions encompassed market penetration, product development, diversification, and competitive positioning. By focusing on these areas, JomRun Sdn. Bhd. can enhance its market presence and sustain its competitive advantage. In conclusion, my internship at JomRun Sdn. Bhd. as a Marketing Intern has provided me with invaluable practical know ledge and skills in marketing activities. I express m y sincere gratitude to Puan Norazamimah for her continuous support and guidance and to Ms. Jasmine Tan Qian Hui for her invaluable mentorship. Their expertise and dedication have significantly shaped m y training experience, preparing me for a successful career in marketing. This internship has laid a strong foundation and equipped me with the necessary skills to excel in the marketing industry. I am confident that the know ledge and experiences gained during this training will greatly contribute to my future endeavours.